DEVELOPMENT OF GENERAL CULTURE IN PRESCHOOL TEACHERS BY MEANS OF MULTIMEDIA - Khodunovа Victoriia (Proceedings of National Aviation University (archive), 2019)
Purpose: The paper addresses the topical issues of general culture development in preschool teachers through multimedia. It is revealed the main directions for their professional development and personal enhancement. The article also reveals the possibilities of using interactive technologies in the development of preschool teachers` general culture. They are determined by the constant growth of scientific psychological-pedagogical and professional information scope needed to maintain the required professional and general cultural level of teachers; the variability expansion of education content, methods, and teaching aids (multifunctional technical means) requiring educators to make choices in order to use them effectively; increasing influence on children of uncontrolled information flows coming from mass media and the need to take into account the opportunities of media education in preparing children for life in the information society with new requirements which brings society closer to the teaching profession and is characterized by its involvement in the active pedagogical search. Methods: the theoretical method was used as a basis for the research. Results: developed modern scientific views on the problem in question are analyzed. The article describes the concepts of “computer technology”, “computer as a teaching aid”, “multimedia training tools”. The peculiarities of the use of multimedia technologies as a means of organizing pre-school education professionals` training in postgraduate education are identified. Discussion: the development of general culture in preschool teachers by means of multimedia is a necessary component of their continuing education as well as the systematic formation of information culture.